Effectiveness of Digital Technology on Biology Learners at the Secondary Level - Choudhuri, Bichitra; Husain, Ahrar (SCHOOL SCIENCE, 2017)
Development and usage of digital classroom for teaching and learning process is one of the key areas for development of ICT in schools. An Interactive White Board (IWB) facilitates teaching in digital classroom and is an instructional tool that allows computer images to be displayed onto a board using a digital projector. The study was an attempt to investigate the effect of digital classroom on learning biology concept of secondary school learners of government and private schools of Delhi. It was a Pre-test Post-test Control Group Design. Using digital classroom, the experimental group was taught. Five chapters of Class IX Biology, i.e., 35 lessons were delivered using interactive white board while the control group was taught by traditional chalk and talk method. Pre-test was consisting of 30 items and post-test consisting of 100 items. Data was collected and analysed by using t-test. Result showed that digital classroom has positive impact on learning process as the learners of digital classroom have higher achievement level in biology in comparison to the learners of traditional classroom. In both, government as well as in private school, the learners taught through digital classroom have higher achievement level in the post-test in comparison to learners taught in traditional method.